Novel method of residual stress reduction for AlSi10Mg manufactured using selective laser melting without compromise of mechanical strength - Lim, Chong Heng (2023)
AlSi10Mg is often used to fabricate functional parts by Laser Beam Powder Bed (LBPB) fusion but is limited by the residual stresses formed during the process. Conventional methods of stress relief of AlSi10Mg often compromise the mechanical properties due to the high-temperature used. This paper solves the dilemma by using a novel method of residual stress relief without compromising its mechanical properties. This process uses a lower temperature for treatment followed by uneven cooling, inducing thermal stress during the cooling process such that it cancels out the existing residual stress that remains. The compressive strength of the part was not compromised after this treatment, verified by microstructure images. From electron backscatter diffraction (EBSD) analysis, the change in density of low angle grain boundaries (LAGB) and magnitude of residual stress relieved via this method followed the same trend, indicating the induction of dislocations from the stress-induced during uneven cooling.